2016
DOI: 10.1007/s10534-016-9963-z
|View full text |Cite
|
Sign up to set email alerts
|

Decreased snake venom metalloproteinase effects via inhibition of enzyme and modification of fibrinogen

Abstract: Since the introduction of antivenom administration 120 years ago to treat venomous snake bit, it has been the gold standard for saving life and limb. However, this therapeutic approach is not always effective and not without potential life-threatening side effects. We tested a new paradigm to abrogate the plasmatic anticoagulant effects of fibrinogenolytic snake venom metalloproteinases by modification of fibrinogen with iron and carbon monoxide and by inhibiting these Zn(2+) dependent metalloproteinases direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(68 citation statements)
references
References 26 publications
2
66
0
Order By: Relevance
“…Alteration of the human fibrinogen molecule has been shown to create resistance to venom‐induced hypocoagulability . Nielsen et al showed that pre‐incubating normal human plasma with CORM‐2 and ferric chloride (FeCl 3 ) mitigated the deleterious effects of venom from both North American and non‐North American vipers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alteration of the human fibrinogen molecule has been shown to create resistance to venom‐induced hypocoagulability . Nielsen et al showed that pre‐incubating normal human plasma with CORM‐2 and ferric chloride (FeCl 3 ) mitigated the deleterious effects of venom from both North American and non‐North American vipers.…”
Section: Discussionmentioning
confidence: 99%
“…Rattlesnake envenomation occurs frequently in dogs throughout the United States and often causes coagulopathy. Rattlesnake venom decreases fibrinogen function by abnormally cleaving fibrinogen alpha and beta chains and rendering it poorly functional for polymerization . In general, antivenom lessens coagulopathy induced by crotalid species; however, it is expensive (especially if multiple doses are necessary), time‐sensitive and poorly available, and some formulations have a short half‐life .…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the concentration of CatroxMP-II used, the onset of coagulation had to be double and/or the velocity of clot formation half of plasma without CatroxMP-II addition to be acceptable for experimentation. The following elastic modulus-based parameters previously described (Nielsen 2018; Nielsen and Bazzell 2016, 2017; Nielsen et al 2016, 2018a, b; Nielsen and Losada 2017; Nielsen and Matika 2017) were determined: time to maximum rate of thrombus generation (TMRTG): this is the time interval (minutes) observed prior to maximum speed of clot growth; maximum rate of thrombus generation (MRTG): this is the maximum velocity of clot growth observed (dynes/cm 2 /second); and total thrombus generation (TTG, dynes/cm 2 ), the final viscoelastic resistance observed after clot formation. Data were collected for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…It has been recently demonstrated that the hemotoxic venom activity of several species of snakes can be inhibited in vitro and in vivo by exposure to carbon monoxide (CO) via thrombelastography (Nielsen 2018; Nielsen and Bazzell 2016, 2017; Nielsen et al 2016, 2018a, b; Nielsen and Losada 2017; Nielsen and Matika 2017). Also of interest, an agent that causes metheme formation (Nielsen et al 2011a) used to identify fibrinogen as a heme binding protein (Nielsen et al 2011b) was demonstrated to decrease the prothrombotic activity of Oxyuranus microlepidotus venom (Nielsen et al 2018a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation